ALIH KODE BAHASA JAWA DALAM INTERAKSI KELAS DI MA ASSULAIMANIYAH MOJOAGUNG - Rani Jayanti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
The code switching reflects the dimension of social distance, status relationship, or the level of formality of the interaction of speakers (Holmes, 2001). This study focuses on the study of code switching with the object of class interaction in MA Assulaimaniyah Mojoagung. The purpose of this study is to explain the factors that cause a code switching of Javanese language in class interaction in MA Assulaimaniyah Mojoagung. The theory of Fishman's code switching (1967) was used in the analysis of this study. This research is a qualitative research which the data were Javanese code switching. Data analysis techniques used are techniques developed by Miles and Huberman (1984), covering three steps, namely (1) data reduction, (2) data presentation, and (3) conclusion or verification. The result of the research shows that the factor of the code switching of the Java language in class interaction in MA Assulaimaniyah Mojoagung includes: a) speaker or speaker, b) listener or spokesman, c) change of situation due to third person presence, d) formal to informal or on the contrary, e) changing the subject, f) to awaken a sense of humor. Keywords: code switching, Cause Factor, MA Assulaimaniyah